Peran TNI dalam Penanggulangan Bencana Alam - Mursyid (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2023)
In writing this journal the author uses a library research method where the data obtained by the author comes from conclusions in previous journals and also through newspapers and books. In this writing method it is often called library research analysis. Where the results of this research can be seen that Indonesia is an archipelagic country whose geographical location makes Indonesia a country that is prone to disasters, BNPB states that Indonesia is a country that has the most comprehensive types of disasters in the world, disasters that arise of course cause a lot of losses and victims. Therefore, to handle disasters both before and after a disaster, good cooperation between related agencies is needed, for example the TNI. The problem formulation in writing this journal is (1) the role of the TNI in the natural disaster management process, (2) what obstacles the TNI faces in the process of evacuating victims of natural disasters and (3) the efforts made by the TNI in handling natural disasters. And the conclusions of this journal are (1) the role of the TNI in the natural disaster management process is that the TNI plays a role in assisting the process of rescuing and evacuating victims, the TNI plays a role in fulfilling the basic needs of protection for vulnerable groups, handling refugees and playing an active role in selecting and repairing infrastructure other general matters, assisting in the process of cleaning up building debris and as a facilitator in providing training, guidance and technical support to the community in building the resilience of a village or area. (2) the obstacles faced by the TNI in evacuating victims were power outages which limited communication, lack of heavy equipment due to impassable roads, unpredictable weather conditions (3) and the efforts made by the TNI in handling natural disasters were by creating a program called disaster resilient village where the implementation of this disaster resilient village is by carrying out the process of collecting data along with disaster risk analysis in a village, forming a disaster response team consisting of TNI and community members, conducting training and outreach to the community about mitigation and handling. disasters and implementing emergency response and disaster recovery programs.